Public telecommunication services and the environmental requirements for the development of its infrastructure - Caballero Fernández, Cyndel (2021)
This article describes the main environmental obligations for the implementation of infrastructure for the provision of public telecommunication services like the obtaining of environmental management instruments, the compliance of maximum permissible limits and environmental principles. The purpose of the referred measures is to prevent that this activity causes significant negative impacts on the environment, natural resources, and people’s health.